CompTIA Security+ (SY0-601) Cert Prep: 4 Identity and Access Management Design and Implementation. - Chapple, Mike (linkedin.com, 2020)
Discover how to create and implement a robust identity and access management system as you prepare to tackle version SY0-601 of the CompTIA Security+ exam.